Encyclopedia of Analytical Chemistry 2012
DOI: 10.1002/9780470027318.a9297
|View full text |Cite
|
Sign up to set email alerts
|

NMRSpectroscopy in Liquid Crystalline and Ordered Phases

Abstract: Applications of nuclear magnetic resonance (NMR) spectroscopy as an analytical tool in liquid crystals (LCs) are surveyed. Proton, deuteron, carbon‐13, and nitrogen‐14 are commonly used as probes in solid‐state NMR of condensed phases. Their usages in LCs are discussed in some details. Complex mathematical expressions needed to interpret NMR observables (both equilibrium and dynamic properties) are kept to a minimum, and the reader can refer to original articles and books for details. As it is impossible to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 234 publications
0
10
0
Order By: Relevance
“…3, with the new carbon peak assignments were analyzed to find S and D for the five-ring core. [33] It was found that to properly obtain molecular order from 13 C chemical shifts in a mesomorphic phase, a way to theoretically predict the relative positions of carbon peaks in the 13 C spectrum would be very useful.…”
Section: Nmr Of A131mentioning
confidence: 99%
“…3, with the new carbon peak assignments were analyzed to find S and D for the five-ring core. [33] It was found that to properly obtain molecular order from 13 C chemical shifts in a mesomorphic phase, a way to theoretically predict the relative positions of carbon peaks in the 13 C spectrum would be very useful.…”
Section: Nmr Of A131mentioning
confidence: 99%
“…(95) and the CSA tensors given in Ref. [228] to fit 21 smoothed aromatic < δ i > k data, the resulting fits were found to be better than previously reported fits most likely due to slightly improved peak assignments [292]. The derived order parameters S and D are plotted versus the temperature in Fig.…”
Section: Conformational Problem Of Bcms: a Case Studymentioning
confidence: 74%
“…9 of Ref. [292]. Their derived S for the dominant Γ 1 conformer had a linear T dependence, likely owing to the aforementioned assumption, in contrast to the expected temperature trend predicted by Maier-Saupe theory [42].…”
Section: Conformational Problem Of Bcms: a Case Studymentioning
confidence: 87%
See 1 more Smart Citation
“…NMR spectroscopy has been highly useful in the study of such systems because it has been shown to provide information with atomistic resolution. [8,9] Although nuclei like 1 H, 2 H, and 19 Fh ave been utilized for investigating such systems, [10][11][12][13] in recent years the naturalabundance 13 CNMR spectroscopict echnique is being increasingly used due to the fact that this approach does not require special sample preparation, such as isotope labeling, and provides high-resolution spectra in the oriented phase. [14][15][16][17][18][19][20][21] It is possible to obtain two anisotropic parameters from 13 CNMR spectroscopy.T he first is the alignment-induced chemical shift (AIS), which is the difference in the chemical shift of the carbon in the isotropic phase to that in the liquid crystalline phase, and arises from the alignment of the molecule in the magnetic field.…”
Section: Introductionmentioning
confidence: 99%